Exploring the Effect of the COVID-19 Pandemic on the Dental Team: Preparedness, Psychological Impacts and Emotional Reactions - Humphris, Gerry; Knights, Jennifer; Beaton, Laura; Araujo, Marianna; Yuan, Siyang; Clarkson, Jan; Young, Linda; Freeman, Ruth (Frontiers in Oral Health, 2021)
Background: The COVID-19 pandemic has placed increased demands on clinical staff in primary dental care due to a variety of uncertainties. Current reports on staff responses have tended to be brief enquiries without some theoretical explanation supported by developed measurement systems. Aim: To investigate features of health and well-being as an outcome of the uncertainties surrounding COVID-19 for dentists and dental health professionals in primary dental care and for those in training. Methods: A cross-sectional survey of dental trainees and primary dental care staff in Scotland was conducted in June to October 2020. Assessment was through ‘Portal’, an online tool used for course bookings/management administered by NHS Education for Scotland. The questionnaire consisted of four multi-item scales including: preparedness (14 items of the DPPPS), burnout (the 9 item emotional exhaustion subscale and 5 items of the depersonalisation subscale of the MBI), the 22 item Impact of Event Scale-Revised, and depressive symptomatology using the Patient Health Questionnaire-2. Analysis was performed to compare the levels of these assessments between trainees and primary dental care staff and a theoretically based path model to explain depressive symptomology, utilizing structural equation modelling. Results: Approximately, 27% of all 329 respondents reported significant depressive symptomology and 54% of primary care staff rated themselves as emotionally exhausted. Primary care staff (n=218) felt less prepared for managing their health, coping with uncertainty and financial insecurity compared with their trainee (n=111) counterparts (all p’s < 0.05). The overall fit of the raw data applied to the theoretical model confirmed that preparedness (negative association) and trauma associated with COVID-19 (positive association) were significant factors predicting lowered mood. Burnout was indirectly implicated and a major path from trauma to burnout was found to be significant in primary care staff but absent in trainees (p < 0.002). Conclusion: These initial findings demonstrate the possible benefit of resourcing staff support and interventions to assist dental staff to prepare during periods of high uncertainty resulting from the recent COVID-19 pandemic.